DISCOVERING THE IMPLIED MEANING OF SIGNS USED IN TOOTHPASTE ADVERTISEMENT VIDEOS - I Ketut Kartiawan; Desak Putu Eka Pratiwi; I Wayan Juniartha (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2022)
Companies use advertisements to promote their products and send particular messages for the target audiences. An advertisement is a piece of text that tells people about something which includes persuading people to buy a product or service. In general, an advertisement is used to introduce a product by a certain company since it has the power to influence and persuade people to do particular action. Signs are commonly used in advertisements so that it is attractive and can convey messages efffectively. This study aimed to analyze the meaning of verbal and non-verbal signs which found in Colgate toothpaste advertisement videos. This study used Colgate toothpaste advertisement videos which taken from YouTube. The theories used in this study are the semiotic theory by Saussure (1983) to determine verbal and non-verbal signs and the theory of meaning by Barthes (1977) to discover the implied meaning of verbal and non-verbal signs found in Colgate toothpaste advertisements. This study uses the descriptive method to analyze the data. As the result, the advertisements show the verbal and visual signs support the company in promoting and informing its product. In this study, connotative meaning occurred dominantly rather that denotative meaning because the advertisements used more hidden meanings rather than literal meaning to convey the messages toward the audiences.